The Evaluation of Chrysanthemum Clones Under Low Elevation - Lia Sanjaya; Budi Marwoto; Kurniawan Budiarto; Eka Fibrianty (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Cultivation of chrysanthemum at low elevation was one effort to expand potential production areas. Under these circumstances, several environmental conditions might not be as conducive as in highland and deviate the plant from the original characters and potential yield. Fifteen promising variants derived from an unconventional breeding program were evaluated at two different elevations; 1200 and 250 m above sea level (asl) at Cianjur-West Java, Indonesia during hot season from April to September 2016. The experiment was designed as progenital selection to seek the adaptive genotypes on the targeted sites. The results showed that varietal differences existed among the tested clones when grown under highland and lowland. At lowland (250 m asl), all clones showed growth retardation expressed by the reduction of flower qualities with different degrees among genotypes. In standard group, only 2015-9 and 2015-15 that produced unchanged flower color, with acceptable plant height standard for cut flower. While in spray type, all tested clones produced flower with degraded floret color.